Pembuatan Game Bamboo Menggunakan Aplikasi Unity 3D - noval kustriawan; Timothy Ronaldy (Politeknik Negeri Batam, 2019)
The Making 3D games that can provide knowledge not only provide entertainment, but one of them aims as knowledge and give a positive impact for lovers of gaming applications. In this case Bamboo game can introduce more about the Indonesian war tool to fight the former colonizers in the form of bamboo. It can be seen in terms of characters, backround, tools used characters and stories that introduce bamboo used by the fighters as a means of war to fight the invaders. In making bamboo game writer use unity 3D application where this application facilitate writer in making. In addition to the manufacture of game writers using a combination of software development methodology and multimedia development. Case diagrams, resistance diagrams, sequence diagrams, class diagrams. To find out how interesting the game the author performs a questionnaire analysis and uses T-Test to perform analysis, from the results obtained no changes before and after playing bamboo games.